Virtual Target Based Terminal Guidance Law for Cruise Projectile Considering Impact Angle Constraint - Li, Guanlin; Yang, Qiangwei; Huang, Xudong (Chinese Control Conference, 2023)
To enhance the impact angle and strike accuracy for the cruise projectile, the finite-time terminal guidance law based on virtual target is proposed in this paper. Firstly, the relative motion between the missile and the target is established. To simplify the problem, the influence caused by maneuvering target is regarded as disturbance, which can be compensated by the robustness of the guidance law. Then, the virtual target is employed with time-varying velocity and the finite-time guidance law is proposed. After that, the stability analyze is carried out based on Lyapunov stability theorem. At last, the effectiveness of the guidance law is testified by the numerical simulations. The comparison results show that lower energy consumption and weaker variation range of LOS rate can be obtained when the guidance law presented in this paper is used.